Effect of Pre- and Postoperative Phenylbutazone and Morphine Administration on the Breathing Response to Skin Incision, Recovery Quality, Behavior, and Cardiorespiratory Variables in Horses Undergoing Fetlock Arthroscopy: A Pilot Study - Conde Ruiz, Clara; Cruz Benedetti, Inga-Catalina; Guillebert, Isabelle; Portier, Karine Genevieve (Frontiers in Veterinary Science, 2015)
This prospective blinded randomized study aimed to determine whether the timing of morphine and phenylbutazone administration affects the breathing response to skin incision, recovery quality, behavior, and cardiorespiratory variables in horses undergoing fetlock arthroscopy. Ten Standardbred horses were premedicated with acepromazine (0.04 mg kg−1 IM) and romifidine (0.04 mg kg−1 IV). Anesthesia was induced with diazepam (0.05 mg kg−1) and ketamine (2.2 mg kg−1) IV at T0. Horses in group PRE (n = 5) received morphine (0.1 mg kg−1) and phenylbutazone (2.2 mg kg−1) IV after induction and an equivalent amount of saline after surgery. Horses in group POST (n = 5) received the inversed treatment. Anesthesia was maintained with isoflurane 2% in 100% oxygen. Hypotension (mean arterial pressure <60 mmHg) was treated with dobutamine. All horses breathed spontaneously. Dobutamine requirements, respiratory rate (fR), heart rate (HR), mean arterial blood pressure, end-tidal CO2, inspired (i) and expired (e) tidal and minute volume (VT and V˙E), inspiratory time (IT), and the inspiratory gas flow (VTi/IT) were measured every 5 min. Data were averaged during four 15 min periods before (P1 and P2) and after the incision (P3 and P4). Serial blood–gas analyses were also performed. Recoveries were unassisted, video recorded, and scored by three anesthetists blinded to the treatment. The postoperative behavior of the horses (25 demeanors), HR, and fR were recorded at three time points before induction (T0–24 h, T0–12 h, and T0–2 h) and six time points after recovery (TR) (TR + 2, 4, 6, 12, 24, 48 h). Data were compared between groups using a Wilcoxon test and within groups using a Friedman test or a Kruskal–Wallis signed-rank test when applicable. Tidal volumes (VTe and VTi) were higher in PRE than in POST during all the considered periods but the difference between groups was only significant during P2 (VTe in mL kg−1 in PRE: 13 [9, 15], in POST: 9 [8, 9], p = 0.01). None of the other variables were significantly different between and within groups. Under our experimental conditions, skin incision did not affect respiratory variables. Administration of pre- versus postoperative phenylbutazone and morphine did not influence recovery quality, HR, fR, or animal behavior.